KAJIAN FERMENTASI PADA BEKASAM SEBAGAI KULINER TRADISIONAL KHAS KOTA AGUNG, TANGGAMUS, LAMPUNG SEBAGAI REFERENSI PEMBELAJARAN BIOTEKNOLOGI KONVENSIONAL - Tira Melani; Aulia Cantika; Nur Fadilla Joda; Khilmia Mufarida; Made Anisa Indrayeni; Kanaya Syaftia Azzahra; Nurul Rahmadina Azzahra; Berti Yolida; Rini Rita T. Marpaung (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the fermentation process of bekasam as a culinary identity of the Kota Agung community in Lampung, which forms part of Lampung culture, whilst linking it to the Phase D Conventional Biotechnology module as a reference source. This study employs a qualitative descriptive approach, with data collected through observation, in-depth interviews, and a literature review. The results of the study indicate that bekasam is a traditional fish fermentation product made from simple ingredients such as fish, salt, and a carbohydrate source, and involves the activity of lactic acid bacteria under anaerobic conditions. This process results in a decrease in pH, the formation of a characteristic sour aroma and taste, the inhibition of spoilage microorganisms, and an increase in the product’s shelf life. In addition to its nutritional and cultural value, bekasam also has potential as a source of ethnoscience-based science education as it is closely linked to community life and can easily be related to conventional biotechnology concepts. Thus, bekasam can be utilised as a contextual learning medium that supports students’ understanding of biotechnology applications in their local environment and strengthens their appreciation of Lampung’s local wisdom.